Influence of process pressures on filling behavior of tubular fabrics in bladder-assisted resin transfer molding. (2nd October 2017) - Schillfahrt, Christian; Fauster, Ewald; Schledjewski, Ralf
Abstract: Among the family of liquid composite molding techniques, bladder-assisted resin transfer molding (BARTM) enables efficient manufacturing of hollow composite parts based on tubular reinforcing textiles. However, resin injection under certain processing conditions can result in high filling times or improper parts and finding the optimal process parameters is often a difficult task. This paper studies the impregnation behavior of a biaxial braided fabric in pressure-driven BARTM under a wide range of injection and bladder pressures. Saturation experiments were accomplished by means of a specifically developed injection test rig comprising an under-sized elastomeric bladder and a monolithic transparent mold. The results obtained show significant influence of the relevant process parameters on local preform compaction, apparent global permeability and filling time. Based on the experiments, a universal moldability diagram was derived that enables identification of admissible and critical operating conditions in BARTM, which supports the finding of optimal part filling settings. Abstract :